Views of Turkish EFL teacher trainees toward technology-integrated PBL practices - Yasemin Kırkgöz; Burcu Turhan (English Language Teaching Educational Journal, 2021)
Problem-Based Learning (PBL) is increasingly becoming popular in teacher education, just like the prevalence in the use of Modular Object Oriented Dynamic Learning Environment (Moodle) which is an instructional socio-constructivist online tool providing collaborative learning. PBL where learning occurs through real-life problem solving practices is also included in the constructivist approach. This study was designed as a mixed methods research which English as Foreign Language (EFL) teacher trainees were involved in PBL through Moodle with the aim of solving problems related to language teaching and learning which they encountered at practicum schools. Participants were 93 EFL teacher trainees studying at a state university in Turkey. The study aimed to reveal the participants’ views of their PBL experiences within the scope of a Materials Evaluation and Adaptation Course. Data were collected through questionnaires and interviews; and analyzed through descriptive statistics and content analysis consecutively. Results demonstrated that the teacher training activities delivered through PBL yielded promising benefits for EFL teacher trainees’ professional development despite some minor flaws faced in the process. Thus, PBL can be considered as a useful method to deliver such courses offered in any branches of teacher education.